Social accountability and nursing education in South Africa - Armstrong, S.J; Rispel, L.C (My University, 2015)
BACKGROUND: There is global emphasis on transforming health workforce education in support of universal health coverage. OBJECTIVE: This paper uses a social accountability framework, specifically the World Health Organization's six building blocks for transformative education, to explore key informants' perspectives on nursing education in South Africa. METHODS: Using a snowballing sampling technique, 44 key informants were selected purposively on the basis of their expertise or knowledge of the research area. Semi-structured interviews were conducted with the key informants after informed consent had been obtained. The interviews were analysed using template analysis. RESULTS: South Africa has strategic plans on human resources for health and nursing education, training, and practice and has a well-established system of regulation and accreditation of nursing education through the South African Nursing Council (SANC). Key informants criticised the following: the lack of national staffing norms; sub-optimal governance by both the SANC and the Department of Health; outdated curricula that are unresponsive to population and health system needs; lack of preparedness of nurse educators; and the unsuitability of the majority of nursing students. These problems are exacerbated by a perceived lack of prioritisation of nursing, resource constraints in both the nursing education institutions and the health training facilities, and general implementation inertia. CONCLUSION: Social accountability, which is an essential component of transformative education, necessitates that attention be paid to the issues of governance, responsive curricula, educator preparedness, and appropriate student recruitment and selection.
KIM
Keywords: Nurses; South Africa; Education, Nursing; Social Responsibility